Neurological health and premature ovarian insufficiency – pathogenesis and clinical management - Słopień, Radosław (Menopause Review/Przegląd Menopauzalny, 2018)
Premature ovarian insufficiency (POI) is related to neurological problems through neurological symptoms of oestrogen deficiency, diseases caused by oestrogen deficiency, and neurological genetic diseases. Neurological symptoms of oestrogen deficiency are usually reported as climacteric symptoms. Diseases caused by oestrogen deficiency are dementia, cognitive decline, and Parkinsonism. Among genetic neurological disorders, ovarioleukodystrophy and fragile X-associated tremor/ataxia syndrome (FXTAS) are reported.